The uses of Wolfram Alpha in Mathematics / Wan Nur Shaziayani Wan Mohd Rosly, Sharifah Sarimah Syed Abdullah and Fuziatul Norsyiha Ahmad Shukri - Wan Mohd Rosly, Wan Nur Shaziayani; Syed Abdullah, Sharifah Sarimah; Ahmad Shukri, Fuziatul Norsyiha (Unit Penerbitan JSKM, 2020)
Wolfram Alpha is a special engine to generate answers and provide more information about the answers given. By using its vast store of expert-level knowledge and algorithms it can automatically answer questions, do analysis and generate reports. Other search engine gives you information, but Wolfram|Alpha gives you the answer. Wolfram|Alpha is ideal for the sort of math that Google's calculator and most other calculator websites couldn't solve the questions given. It even provides graphs that help students understand the mathematical concept itself. According to Flanagan (2008), many educators use a variety of technologies to enhance student interest and achievements. To access Wolfram Alpha, simply go to the link https://www.wolframalpha.com/, then its interface is shown in figure1. The mathematical expressions used in Wolfram Alpha are slightly different from the calculator